Multi-Task Deep Supervision on Attention R2U-Net for Brain Tumor Segmentation - Ma, Shiqiang; Tang, Jijun; Guo, Fei (Frontiers in Oncology, 2021)
Accurate automatic medical image segmentation technology plays an important role for the diagnosis and treatment of brain tumor. However, simple deep learning models are difficult to locate the tumor area and obtain accurate segmentation boundaries. In order to solve above problems, we propose a 2D end-to-end model of attention R2U-Net with multi-task deep supervision (MTDS). MTDS can extract rich semantic information from images, obtain accurate segmentation boundaries, and prevent overfitting problems in deep learning. Furthermore, we propose the attention pre-activation residual module (APR), which is an attention mechanism based on multi-scale fusion methods. APR is suitable for deep learning model to help the network locate the tumor area accurately. Finally, we evaluate our proposed model on the public BraTS 2020 validation dataset which consists of 125 cases, and got a competitive brain tumor segmentation results. Compared with state-of-the-art brain tumor segmentation methods, our method has the characteristics of small parameter and low computational cost.